STUDENTS’ STRATEGIES IN TRANSLATING PHRASE IN 9th GRADE AT SMP SWASTA KENANGA - Raja Daud Simorangkir; Chyntia Tiodora Panjaitan; Resperdiana Purba (English Language Teaching Prima Journal (ELT), 2019)
This research was conducted to Students 9th grade at SMP Swasta Kenanga Medan. There are two aims of this research. They are :(1) to know Students’ strategies of 9th grade at SMP Swasta Kenanga in translating phrase; (2) to make it easier for 9th grade at SMP Swasta Kenanga to understand translating phrase. The findings of this research showed that there are two strategies that students used in translating phrase. They are free translation and word by word. The writer used qualitative as the method for conducting this research. The data are obtained from the Questionnaire. Key Words: Strategy, Translation, and Phrase